2014
DOI: 10.1038/srep04089
|View full text |Cite
|
Sign up to set email alerts
|

Species identification through mitochondrial rRNA genetic analysis

Abstract: Inter-species and intraspecific variations in mitochondrial DNA (mtDNA) were observed in a bioinformatics analysis of the mitochondrial genomic sequences of 11 animal species. Some highly conserved regions were identified in the mitochondrial 12S and 16S ribosomal RNA (rRNA) genes of these species. To test whether these sequences are universally conserved, primers were designed to target the conserved regions of these two genes and were used to amplify DNA from 21 animal tissues, including two of unknown origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
113
1
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(124 citation statements)
references
References 38 publications
2
113
1
8
Order By: Relevance
“…Phyllopezus heuteri is differentiated from P. periosus by irregularly shaped elements of color pattern (versus well defined transversal bands in P. periosus), by spiny scales surrounding the ear opening (versus cycloid scales) ( Figure S12), and by the contact between the two greatly enlarged postmentals (versus enlarged lateral postmentals separated by small median postmentals) ( Figure S13). Phyllopezus heuteri is distinguished from P. pollicaris by the presence of two to three larger scales (tubercle-shaped) at the mouth commissure (versus small homogeneous scales at the mouth commissure in P. pollicaris), lateral body tubercles reaching further downwards (lowermost tubercle at 6-8 lateral scales from ventrals versus [13][14][15], and presence of more tubercles (five to eight) between eye and ear opening (versus up to three) ( Figure S14). Phyllopezus heuteri can be distinguished from P. przewalskii by the presence of tubercles on the prescapular region and sides of the neck (versus homogeneous scalation in P. przewalskii) (Figure S15) followed by a row of five smaller scales; scales under the head gradually reducing in size posteriorly; dorsal and lateral parts of the neck covered with granular juxtaposed scales with irregular rows of tubercles; throat region with juxtaposed and cycloid homogeneous scales; dorsum of the body with granular scales and tubercles approximately 2.5 times the size of the surrounding granular scales, disposed in 8 or 9 irregular rows on each side reaching onto flanks; ventral scales cycloid and imbricate, arranged in 32 longitudinal rows at midbody; limbs covered with granular juxtaposed scales, except on the dorsal surface of the upper arms and thighs that present slightly imbricated scales; forelimbs more slender than hind limbs; infradigital lamellae of hands starting from pollex were recorded as follows: 5/6 -10/9 -10/11 -10/10 -9/8; infradigital lamellae of feet starting from hallux were recorded as follow: 6/5 -10/9 -11/11 -10/12 -8/9; claws enclosed by a sheath of six rows of scales; a single slightly developed postcloacal tubercle on each side; tail with imbricate, cycloid scales that are smaller on the dorsal and larger on the lateral surfaces, and an enlarged median subcaudal row of scales covering most of the ventral surface.…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Phyllopezus heuteri is differentiated from P. periosus by irregularly shaped elements of color pattern (versus well defined transversal bands in P. periosus), by spiny scales surrounding the ear opening (versus cycloid scales) ( Figure S12), and by the contact between the two greatly enlarged postmentals (versus enlarged lateral postmentals separated by small median postmentals) ( Figure S13). Phyllopezus heuteri is distinguished from P. pollicaris by the presence of two to three larger scales (tubercle-shaped) at the mouth commissure (versus small homogeneous scales at the mouth commissure in P. pollicaris), lateral body tubercles reaching further downwards (lowermost tubercle at 6-8 lateral scales from ventrals versus [13][14][15], and presence of more tubercles (five to eight) between eye and ear opening (versus up to three) ( Figure S14). Phyllopezus heuteri can be distinguished from P. przewalskii by the presence of tubercles on the prescapular region and sides of the neck (versus homogeneous scalation in P. przewalskii) (Figure S15) followed by a row of five smaller scales; scales under the head gradually reducing in size posteriorly; dorsal and lateral parts of the neck covered with granular juxtaposed scales with irregular rows of tubercles; throat region with juxtaposed and cycloid homogeneous scales; dorsum of the body with granular scales and tubercles approximately 2.5 times the size of the surrounding granular scales, disposed in 8 or 9 irregular rows on each side reaching onto flanks; ventral scales cycloid and imbricate, arranged in 32 longitudinal rows at midbody; limbs covered with granular juxtaposed scales, except on the dorsal surface of the upper arms and thighs that present slightly imbricated scales; forelimbs more slender than hind limbs; infradigital lamellae of hands starting from pollex were recorded as follows: 5/6 -10/9 -10/11 -10/10 -9/8; infradigital lamellae of feet starting from hallux were recorded as follow: 6/5 -10/9 -11/11 -10/12 -8/9; claws enclosed by a sheath of six rows of scales; a single slightly developed postcloacal tubercle on each side; tail with imbricate, cycloid scales that are smaller on the dorsal and larger on the lateral surfaces, and an enlarged median subcaudal row of scales covering most of the ventral surface.…”
Section: Diagnosismentioning
confidence: 99%
“…Molecular data are now often used for species identification [12][13][14] and species delimitation [15][16][17][18] helping taxonomists to improve the global knowledge of alpha taxonomy. This led to the recognition of many cryptic phylogenetic lineages of reptiles in the Neotropics [9,19].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that mtDNA 12S and 16S rRNA genes have been used extensively as molecular markers to categorize mammals, birds, shrimp and other species (Kitano et al 2007;Yang et al 2014). DNA sequence of 12S and 16S rRNA showed high variability when compared to other DNA markers since this region is reported as highly conserved (Wang et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial DNA 12S and 16S rRNA genes cover 1/16 and 1/10 of entire mitochondrial genome, respectively (Yang et al 2014). Due to high mutation rate of mtDNA in most animals, it contributes to a significant amount of sequence variation in identification of closely related species (Yang et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation